PICTURE BOOKS AS A MEDIUM FOR TEACHING CULTURAL UNDERSTANDING IN PRIMARY EFL CLASSES - Choriyeva , Oysha (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This study explores the effectiveness of picture books as a pedagogical medium for teaching cultural understanding in elementary-level English as a Foreign Language (EFL) classrooms. Conducted with 2nd-grade pupils at a primary school in Tashkent, Uzbekistan, the research aimed to determine how picture books can help children develop cross-cultural awareness and positive attitudes toward diversity. Using innovative, child-centered strategies—such as visual exploration, guided discussion, dramatization, creative drawing, and culture comparison charts—the study examined students’ progress over a 12-week period. Qualitative and quantitative data were gathered through observation, interviews, and pre-/post-assessments. Findings show that picture books significantly enhance pupils’ comprehension of cultural diversity, curiosity about global traditions, and willingness to communicate in English. The study concludes that visual narratives provide a powerful, age-appropriate way to integrate culture and language learning in EFL classrooms.